1987
DOI: 10.1002/jnr.490170211
|View full text |Cite
|
Sign up to set email alerts
|

Acidic phospholipids, diacylglycerols, and free fatty acids in gerbil brain: A comparison of ischemic changes resulting from carotid ligation and decapitation

Abstract: The levels of brain acidic phospholipids (poly-PI, PI, PA, and PS), DG, and FFA and their acyl group profiles were determined after induction of ischemia in gerbils by ligation of the common carotid arteries and decapitation. Ischemia induced by both procedures resulted in a significant decrease in poly-PI (20% for 1-min decapitation and 1-min ligation). Except for a 16% increase in PI in the 5-min decapitation group, no apparent change was found in other phospholipids after either ischemic condition. The leve… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

2
4
0

Year Published

1988
1988
1997
1997

Publication Types

Select...
5
2

Relationship

0
7

Authors

Journals

citations
Cited by 14 publications
(6 citation statements)
references
References 21 publications
2
4
0
Order By: Relevance
“…The loss of 150 nmol of PIP2 during ischemia is not accounted for by a gain in free 20:4 acid, free 18:O acid, and DG. This observation is in agreement with a recent report of changes in gerbil brain lipids following decapitation (Huang and Sun, 1987). This pool of PIP,, which represents -50% of the total loss, may be degraded to phosphatidylinositol-4-phosphate and phosphatidylinositol via phosphatases.…”
Section: Discussionsupporting
confidence: 93%
See 2 more Smart Citations
“…The loss of 150 nmol of PIP2 during ischemia is not accounted for by a gain in free 20:4 acid, free 18:O acid, and DG. This observation is in agreement with a recent report of changes in gerbil brain lipids following decapitation (Huang and Sun, 1987). This pool of PIP,, which represents -50% of the total loss, may be degraded to phosphatidylinositol-4-phosphate and phosphatidylinositol via phosphatases.…”
Section: Discussionsupporting
confidence: 93%
“…This source may be phosphatidylinositol or phosphatidylinositol-4-phosphate via phospholipase C, or triacylglycerol or phosphatidic acid via triacylglycerol lipase or phosphatidic acid phosphohydrolase. In fact, in rat brain, the triacylglycerol and phosphatidic acid pools are enriched in saturated fatty acids and have been suggested as a source for saturated DG accumulation during ischemia (Aveldaiio and Bazan, 1975a,b;Ikeda et al, 1986;Huang and Sun, 1987). A likely candidate for "X' fatty acid is 18: 1 acid, the level of which increases by 89 nmol in the DG pool after ECS.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…We conclude that connections between the posterior and anterior circulations are variable and must be accounted for if a bimodal distribution in results is evident. Other investigators have reported increased fatty acid concentrations in the gerbil ischemiareperfusion model (De Medio et al, 1980;Yoshida et al, 1983Yoshida et al, , 1984 and in rat brain 3 and 15 mm after decapitation (Deutsch et al, 1997), as well as increased lysophospholipids and diglycerides and decreased diphosphophosphatidylinositol (Abe and Kogure, 1986;Huang and Sun, 1987). Our pattern of fatty acid changes agrees with previous reports (De Medio et al, 1980;Yoshida et al,, 1983Yoshida et al,, , 1984Huang and Sun, 1987) and FIG.…”
Section: Discussionsupporting
confidence: 91%
“…The increase in arachidonic acid concentration is relatively higher than for other fatty acids and can contribute to edema (Chan et al, 1985). Fatty acids also are released by combined activation of phospholipase C and diglyceride lipase (De Medio et a!., 1980;Yoshida et al, 1983Yoshida et al, , 1984Rordorf et al, 1991) and by lysophospholipase (Abe and Kogure, 1986;Huang and Sun, 1987) acting on lysophospholipids produced by the activation of phospholipase A 2 (Bonventre and Koroshetz, 1993). Lysolecithin formed by the action of phospholipase A2 on phospholipids can form micelles (Purdon et al, 1975) and destabilize cell membrane bilayers.…”
mentioning
confidence: 99%